Tools for identification of nurses' experiences of inpatient aggression - Zuzana Kadlčková; Martina Tomagová (University of Ostrava, 2018)
Aim: The objective of this review study was to find quantitative research studies that describe nurses' experiences of aggression using scales, and to provide an introduction to these evaluation tools. Design: A review study. Method: Research studies were searched for using keywords in the licensed electronic bibliographic databases CINAHL, Academic Search Complete (EBSCOhost), SCOPUS, PubMed, and Medline from January to May 2017. Results: From the fifty-two found, six relevant studies were included. For the purpose of gaining information about nurses' experiences of inpatient aggression, the following tools were used in these studies: the Violent Incident Form; the Overt Aggression Scale; the Perceptions of Prevalence of Aggression Scale; the Violence and Aggression of Patients Scale; the Survey of Violence Experienced by Staff (German Version-Revised); and Workplace violence. Conclusion: Several reliable measuring tools have been developed for the purpose of measuring nurses' experiences of inpatient aggression. They differ in many characteristics, making comparison of the results found using these measuring tools somewhat more difficult. Another limitation is that the tools assess nursesʼ experiences of aggressive behavior over the period of the previous 12 months, which might affect the accuracy of respondents' memory. These tools are an important method of gaining data on nurses' experiences of inpatient aggression; however, they do not provide precise objective data on patient aggression in clinical practice. Keywords: aggression, experience, hospitalization, measuring tool, nurse, patient.